Macrophage paired receptor interactions - Barclay, Neil (Henry Stewart Talks, 2012)
Immunoregulation and cell surface receptors, Paired receptors, Inhibitory, Activating, Myeloid cells, X-ray crystallography, Protein structure Ig superfamily domains, Evolution Pathogen pressure, Host environment interactions
Reviewed at 2021/10/12